Etude de la commande par logique floue d'un filtre actif parallèle à trois fils. - ATEF, Ghouli; AHMED BACHIR, Karmia (université d'eloued, 2023)
In a low voltage electrical network, harmonics, reactive power, current and voltage imbalances have adverse effects on electrical equipment. This memory presents the study and the control of a parallel active filter for the improvement of the quality of the energy of an electrical network. To this end, a reminder of the different types of electrical disturbances has been produced. The identification is made by the instantaneous power method, the control is carried out by hysteresis and the regulation of the DC bus voltage by fuzzy logic. The simulation results obtained have shown good performance for the proposed control. في الشبكة الكهربائية ذات الجهد المنخفض ، يكون للتوافقيات ، والاستطاعة التفاعلية ، والاختلالات الحالية تأثيرات سلبية على المعدات الكهربائية. تقدم هذه المذكرة الدراسة والتحكم في مرشح نشط متوازي لتحسين جودة الطاقة في الشبكة الكهربائية. تحقيقا لهذه الغاية ، تم إصدار تذكير بأنواع مختلفة من الاضطرابات الكهربائية. يتم التحديد بواسطة طريقة الاستطاعة اللحظية ، ويتم التحكم عن طريق التباطؤ وتنظيم جهد ناقل التيار المستمر بواسطة المنطق الضبابي ، وقد أظهرت نتائج المحاكاة التي تم الحصول عليها أداءً جيدًا للتحكم المقترح.
مذكرات ماستر تخصص ماكينات كهربائية
Keywords: fuzzy logic -parallel active filter; المنطق الضبابي - عامل التصفية النشط الموازي.